Flower-like tungsten-doped Fe–Co phosphides as efficient electrocatalysts for the hydrogen evolution reaction. Issue 26 (22nd June 2021) - Zhang, Qian; Tang, Shuihua; Shen, Lieha; Yang, Weixiang; Tang, Zhen; Yu, Limei
Abstract : In this article, we introduce W into Fe–Co phosphides to optimize the hydrogen adsorption energy thereby accelerating the kinetics of the HER. Abstract : Developing cost-effective and high-performance electrocatalysts for the hydrogen evolution reaction (HER) is imperative thanks to the rapid increase of fuel-cell driven vehicles. Tungsten (W) possesses advantages of optimized hydrogen adsorption energy and improved water adsorption ability, thus we introduce W into Fe–Co bimetallic phosphides by in situ growing W–FeCo hydroxides on nickel foam (NF) via a hydrothermal procedure followed by phosphorization. The as-prepared W–FeCoP/NF catalyst shows a three-dimensional (3D) flower-like morphology, which can facilitate charge transfer and mass transportation. When the molar ratio of W : Fe : Co is 1 : 4 : 8, the catalyst exhibits excellent HER activity with an overpotential of 66 mV at 10 mA cm −2, a Tafel slope of 83 mV dec −1, an electrochemical surface area of 70 mF cm −2, and a R ct of 0.3 Ω in 1.0 M KOH solution. Its performance is much better than that of FeCoP/NF, FeP/NF, or CoP/NF. Meanwhile, the W–FeCoP/NF electrode demonstrates prominent HER catalytic activity at a current density of 800 mA cm −2, and it also exhibits better stability than the FeCoP/NF electrode. The excellent performance can be ascribed to the W–FeCoP/NF electrode with efficient W-doping and unique 3D flower-like structure. This work will provide a strategy to explore a new class of transition metal phosphides with prominent catalytic activity for the hydrogen evolution reaction.